Teoria systemów-światów Immanuela Wallersteina i jej recepcja w archeologii: część III – okres wpływów rzymskich - Ciesielska, Adriana (Folia Praehistorica Posnaniensia, 2019)
Immanuel Wallerstein’s centre-periphery model lies at the root of many archaeological studies, particularly studies of romanisation. One of them has been an article written by Peter S. Wells, but we have also studies done by Richard Higley concerning Roman Britain, Susan Frankenstein and Michael Rowland concerning the social hierarchy in Roman Germany. Actually several archaeologists tried to study these topic according to the Wallerstein’s world-systems theory. We can observe that the application of the theory into archaeology has always very important heuristic value.